Postcolonial Studies: Hybridity and the Dominance of Whites over Blacks in American Poetry - Yuli Wahyuni; Diyah Iis Andriani (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study aims to reveal the postcolonial issues contained in poetry I, Too by Langston Hughes and Incident by Countee Cullen. Both authors of these poems are figures from black people in America. The method used in this study is the qualitative method and literature study approach with the aim of exploring, describing, and understanding how the hybridity and dominance of whites over blacks in American poetry. The data source of this study is the words and phrases in both poems. The data containing postcolonial: hybridity and mimicry in the poems were characterized and analyzed using Homi K. Bhabha's theory (2007). Bhabha in his thinking tries to provide a "middle space" between the colonizer and the colonized. Bhabha states the concept of a “middle space” as a time-lag. This space is an intercultural space where personal and communal self-defense strategies can be developed. All of these cultural expressions and systems are built in a space called the “third space of enunciation”. Interestingly, the issue of hybridity that occurred a century ago has not completely gone in a better direction. The proof is that at the beginning of the first semester of 2020 there was an incident of violence against blacks by whites which caused a massive demonstration that led to the creation of a movement group called Black Lives Matter. This study uncovers how bad the treatment of white people towards black people is that the position and social stratifications between them are different.